“A Horrible Fascination”: Sex, Segregation, and the Lost Politics of Obscenity - Anders Walker (Washington University Law Review, 2012)
Building on current interest in the regulation of child pornography, this Article goes back to the 1950s, recovering a lost history of how southern segregationists used the battle against obscenity to counter the Supreme Court’s ruling in Brown v. Board of Education. Focused on the psychological development of children, Brown sparked a discursive backlash in the South focused on claims that the races possessed different cultures and that white children would be harmed. This backlash joined a larger, regional campaign, a constitutional guerilla war mounted by moderates and extremists alike that swept onto cultural, First Amendment terrain even as the frontal assault of massive resistance succumbed to federal might. A radical re-reading of prevailing understandings of southern resistance to Brown, this Article posits that civil rights proved much more culturally contingent than scholars have so far recognized and reframes the manner in which we understand Brown, its progeny, and current constitutional debates over the relationship between rights and race.